Evaluation of package inserts of Ayurveda drug formulations from Mumbai city - Shirolkar, Sudatta (Ayu, 2015)
INTRODUCTION: Package insert (PI) is a vital document accompanying a prescribed medication to provide information to the prescriber and end-user at a glance. Studies regarding PIs of Ayurvedic medicines in accordance with standard guidelines are lacking. AIM: Present study was undertaken to evaluate PI of Ayurveda drugs. MATERIALS AND METHODS: PIs of Ayurveda drugs were obtained from five randomly selected Ayurveda medical shops located in three main zones of Mumbai. From each medical shop, a range of 15–20 PI was planned to be collected for different formulations. It was decided to collect a minimum fifty PIs/group for equitable distribution of various formulations in period of January–June2013. Checklist was prepared, and content validity was achieved. Final validated checklist contained a total of 13 items, and the presence or absence of information pertaining to these items on the PI was evaluated. Any other additional information present on PI was also noted. Each item was analyzed and expressed as percentages. RESULTS: The information on 258 PIs included: Name of ingredients (67%), quantity of ingredients (47.27%), route of administration (86.8%), dosage form (86.8%), indications (18%), dose (18%), contraindications (18%), side effects (9%), shelf life (5.81%), storage conditions (11%), and manufacturers name with contact details (34%). CONCLUSION: PIs accompanying Ayurveda medicinal products in India are deficient in information required to be furnished by them.